2012
DOI: 10.6002/ect.2011.0176
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Serum and Bronchoalveolar Lavage Galactomannan in Diagnosing Invasive Aspergillosis in Solid-Organ Transplant Recipients

Abstract: Objectives: This study sought to compare the sensitivities of serum galactomannan and bronchoalveolar lavage galactomannan in diagnosing invasive aspergillosis in solid-organ transplant recipients (lung and heart). Materials and Methods: This study took place in the lung transplant center of the National Research Institute for Tuberculosis and Lung Disease. All patients with clinical and radiologic manifestations suggestive of pulmonary infection were included. Serum and bronchoalveolar lavage galactomannan we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…However, limitations of biopsy make it applicable only to part of patients . In recent years, with a widespread application of serum GM and aspergillus fluorescent PCR tests, early diagnosis of aspergillosis is significantly improved (Springer et al, 2012;Tabarsi et al, 2012). GM test is a method which adopts serum enzyme-linked immunosorbent assay to detect aspergillus galacto-glucomannan antigens, to confirm a diagnosis of aspergillosis (Godet et al, 2012;Reinwald et al, 2012;Stopiglia et al, 2012;Tabarsi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, limitations of biopsy make it applicable only to part of patients . In recent years, with a widespread application of serum GM and aspergillus fluorescent PCR tests, early diagnosis of aspergillosis is significantly improved (Springer et al, 2012;Tabarsi et al, 2012). GM test is a method which adopts serum enzyme-linked immunosorbent assay to detect aspergillus galacto-glucomannan antigens, to confirm a diagnosis of aspergillosis (Godet et al, 2012;Reinwald et al, 2012;Stopiglia et al, 2012;Tabarsi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, with a widespread application of serum GM and aspergillus fluorescent PCR tests, early diagnosis of aspergillosis is significantly improved (Springer et al, 2012;Tabarsi et al, 2012). GM test is a method which adopts serum enzyme-linked immunosorbent assay to detect aspergillus galacto-glucomannan antigens, to confirm a diagnosis of aspergillosis (Godet et al, 2012;Reinwald et al, 2012;Stopiglia et al, 2012;Tabarsi et al, 2012). The sensitivity of GM test was 50-90% and the specificity was 80-90%, and usually demonstrating positive before the emergence of radiological evidence (Horbrecht et al, 2002;Georgiadou et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Cordonnier et al have recently shown that amongst haematology patients with neutrophils levels <0.1 × 10 9 /L are more likely to have higher serum GM levels than patients with higher neutrophil levels [191]. The serum GM assay has been shown to be modestly sensitive in COPD patients with IA [192, 193] and poorly sensitive in solid organ transplantation [194, 195] though more recent studies have achieved greater sensitivities in this patient group [196]. The lower incidence of neutropenia in these two patient groups may well account in part for the reduced sensitivity of the serum GM assay.…”
Section: Galactomannan Detectionmentioning
confidence: 99%
“…Aspergillus GM antigen detection in serum and bronchoalveolar lavage (BAL) fluid by the Bio-Rad Platelia sandwich enzyme immunoassay (EIA, Bio-Rad) has been studied extensively [12,13]. Several previous studies have also evaluated the GM assay in BAL samples in various patient groups and conditions; they reported a higher parallel sensitivity and specificity in comparison to serum specimens [14][15][16]. According to the revised European Organization for Research and Treatment of Cancer and Mycoses Study Group (EORTC/MSG) diagnostic criteria, a positive BAL GM test is a mycological criterion of IA in association with host and clinical or radiological findings [17].…”
Section: Introductionmentioning
confidence: 99%